Selling Communication Strategy: Modes, Models, and Messages - Bambang Sukma Wijaya (Jobmark: Journal of Branding and Marketing Communication, 2024)
Effective selling communication strategies are crucial for marketing success. Communication not only influences consumer purchasing decisions but also fosters long-term relationships between sellers and buyers. Therefore, a deep understanding of persuasive selling communication concepts is essential to optimize marketing strategies. This article constructs a comprehensive concept of persuasive selling communication by integrating various modes, models, and messages employed in sales practice. A narrative review methodology is used to synthesize relevant literature and develop a holistic conceptual framework. The study identifies twelve modes of selling communication: Verbal (spoken and written words), Nonverbal (body language, gesture, facial expression), Paraverbal (tone, pitch, volume, speed, and cadence), Visual (images and symbols), Aural (sounds), Audiovisual (combination of sound and images), Textural (texture, shape), Nasal (smell), Gustatorial (taste), Kinetic (physical movement), Haptic (touch), and Proxemic (distances). Additionally, four dominant selling models are discussed: solution-oriented selling, transactional selling, consultative selling, and provocative selling. Regarding messages, three categories are outlined: hard-selling (aggressive sales tactics), soft-selling (gentle persuasion), and hidden-selling (subtle or implicit selling). The practical implications of these findings provide sales practitioners with guidance on selecting and combining appropriate modes, models, and messages tailored to market contexts and customer characteristics. Academically, this article opens avenues for further research in developing adaptive and innovative selling communication theories.